2023
DOI: 10.1002/iid3.1038
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid proteomics in meningitis patients with reactivated varicella zoster virus

Huili Liu,
Jun Wang,
Yan Zhang
et al.

Abstract: ObjectiveThis study investigated the proteomic characteristics of cerebrospinal fluid (CSF) in patients with varicella zoster virus (VZV) meningitis to understanding the pathogenesis of central nervous system (CNS) infection by reactivated VZV.MethodWe used data‐independent acquisition model to analyze the CSF proteomic differences of 28 patients with VZV meningitis and 11 herpes zoster (HZ) patients. According to the clinical manifestations at discharge, 28 VZV meningitis patients were divided into favorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(96 reference statements)
0
0
0
Order By: Relevance
“…Our study demonstrated elevated serum levels of neurospecific enolase in patients with PHN, potentially indicating the influence of the herpes zoster virus on the central or peripheral nervous system. Peripheral nerve damage caused by the herpes zoster virus is unquestionable, and numerous studies have reported various aspects of herpes zoster virus affecting the central nervous system [ 45 47 ]. The specific underlying mechanism remains unclear and requires further validation through rigorous biological experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated elevated serum levels of neurospecific enolase in patients with PHN, potentially indicating the influence of the herpes zoster virus on the central or peripheral nervous system. Peripheral nerve damage caused by the herpes zoster virus is unquestionable, and numerous studies have reported various aspects of herpes zoster virus affecting the central nervous system [ 45 47 ]. The specific underlying mechanism remains unclear and requires further validation through rigorous biological experiments.…”
Section: Discussionmentioning
confidence: 99%
“…44 NFKBIZ is an important regulator in the NF-κB signaling pathway and is involved in the activation of immune pathways that regulate inflammation cell survival. 45 Genes such as CSF2 46 and PRTN3 47 may also play a regulatory role in the immune system, participating in some aspects of the host defense mechanisms. Therefore, BAPN-1 may play a positive role in enhancing immune activity while exerting its antitumor effects.…”
Section: Homogeneity and Chemical Analysis Of Bapn-1mentioning
confidence: 99%
“…17 Viral reactivation is prevented and VZV infection is managed over the long term by the adaptive immune response, which is mediated by B and T cells. 18 VZV-specific T cells are produced during initial infection and can identify and eliminating virus-infected cells.…”
Section: Introductionmentioning
confidence: 99%